Birds, beasts, and fishes : a selection of animal poems - Carter, Anne.; Cartwright, Reg (New York : Macmillan Pub. Co. : Maxwell Macmillan International Pub. Group, 1991)
An illustrated anthology of animal poems from around the world.
Includes indexes.
School Library Journal starred.
School Library Journal.
Horn Book.
6.9
3-6
Keywords: Animals -- Juvenile poetry; Birds -- Juvenile poetry; Fishes -- Juvenile poetry; Animals -- Poetry; Poetry -- Collections; Animals -- Poetry; Birds -- Poetry; Fishes -- Poetry; Animals -- Poetry; Poetry -- Collections